2004
DOI: 10.1177/0363546503260788
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Natural History of Acute Patellar Dislocation

Abstract: Patellar dislocators who present with a history of patellofemoral instability are more likely to be female, are older, and have greater risk of subsequent patellar instability episodes than first-time patellar dislocators. Risk of recurrent patellar instability episodes in either knee is much higher in this group than in first-time dislocators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
844
1
51

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 987 publications
(918 citation statements)
references
References 57 publications
22
844
1
51
Order By: Relevance
“…Lateral patellofemoral instability is a potentially disabling condition, with an incidence of 5.8 per 100,000, and is even more common in a younger population [9,11]. An increase in the TT-TG distance is one anatomic abnormality that may contribute to this condition [7,29].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral patellofemoral instability is a potentially disabling condition, with an incidence of 5.8 per 100,000, and is even more common in a younger population [9,11]. An increase in the TT-TG distance is one anatomic abnormality that may contribute to this condition [7,29].…”
Section: Introductionmentioning
confidence: 99%
“…Acute patellar dislocation accounts for 2-3% of acute knee injuries, with the highest incidence being in adolescence [1,2]. Apart from the traumatic component, the presence of predisposing morphological and functional patellofemoral disorders [3,4] is of equal importance.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical studies demonstrate incidence of 5.8 per 100,000 inhabitants and this number increases to 29 per 100,000 inhabitants between 10 years and 17 years of age (11,12) . Hsiao et al (8) observed higher incidence of this injury in military privates, who attributed the intrinsic physical fitness of this group and the character of their activities, which make the risks of musculo-skeletal injuries increase, condition which we consider comparable to professional athletes.…”
Section: Discussionmentioning
confidence: 96%